METABOLIC EFFECTS OF FEEDING SUPPLEMENTAL TALLOW TO LACTATING NILI-RAVI BUFFALO - H. Nawaz; M. Abdullah; M. Yaqoob; M. A. Jabbar; M. Sarwar; M. Younas (Journal of Animal and Plant Sciences, 2012)
Four early lactating Nili-Ravi buffaloes were fed four experimental diets containing 0, 2, 4 and 6% tallow in an experiment conducted in a 4x4 Latin Square design to study the effect of feeding different levels of tallow on nutrient intake, digestibility, rumen fermentation and blood metabolites. The intakes of DM, OM, CP, ADF and NDF decreased (P0.05) but acetate content decreased significantly (P<0.01) as the level of dietary tallow increased, whereas, propionate molar percentages increased (P<0.01) with increasing level of tallow in the diets. However, butyrate contents were not statistically different among different treatment groups. Acetate to propionate ratio decreased linearly (P<0.05) with increasing level of tallow in the diets. Blood pH and concentration of glucose did not vary significantly but cholesterol, triglycerides and total lipids increased (P<0.01) as the level of tallow increased in the diets. These results suggest that tallow up to 4% of diet dry matter is a suitable fat supplement as an energy source for lactating Pakistani Nili-Ravi buffaloes.
Keywords: Tallow levels; nutrient intake; digestibility; rumen fermentation; blood metabolites